Wage Gaps and Job Sorting in African Manufacturing - Fafchamps, Marcel; Soderbom, Mans; Benhassine, Najy (2012)
Using matched employer-employee data from eleven African countries, we investigate if there is job sorting in African labour markets. We find that much of the wage gap associated with education is driven by selection across occupations and firms. This is consistent with educated workers being more effective at complex tasks such as labour management. In all countries, the education wage gap widens rapidly at high levels of education. Most of the education wage gap at low levels of education can be explained by selection across occupations. We also find that the education wage gap tends to be higher for women, except in Morocco where many poorly educated women work in the garment sector. A large share of the gender wage gap is explained by selection into low wage occupations and firms.